Benefits of Grandparental Caregiving in Chinese Older Adults: Reduced Lonely Dissatisfaction as a Mediator - Chang, Yuanqing; Li, Yin; Zhang, Xin (Frontiers in Psychology, 2020)
Objective. The purpose of the present study is two-fold: 1) to investigate the differences in terms of physical and mental health between those who provide grand-parental care and those who do not; and 2) to explore the mechanism that connects grandparental caregiving and health-related outcomes. Methods. Two studies (a cross-sectional and a short-term longitudinal follow-up) were conducted. The cross-sectional study (Study 1) examined 148 older adults who provided grandparental care and another 150 older adults who did not. A small longitudinal follow-up study (Study 2) was conducted among 102 older adults randomly selected from Study 1, of which 52 were older adults who provided grandparental care, and another 50 older adults were those who did not. Health status (measured by SF-36), lonely dissatisfaction (measured by Lonely Dissatisfaction Subscale of PGC-MS), cognitive functions (measured by subscales of WAIS), as well as demographics were measured in both studies. Results. Results of both the cross-sectional and longitudinal studies showed that, compared with older adults who did not provide grandparental care, those providing grandparental care had significantly better physical and mental health as well as reduced lonely dissatisfaction. Further path analysis showed that lonely dissatisfaction mediated the association between providing grandparental care and enhancement in functions such that providing grandparental care could reduce lonely dissatisfaction, which in turn could improve their physical and mental health even after controlling for their cognitive functions. Discussion. These results suggested that providing grandparental care can improve older adults’ physical and mental health through reduced lonely dissatisfaction.